2013
DOI: 10.1051/0004-6361/201322104
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of environmental dependencies of Type Ia supernovae from the Nearby Supernova Factory indicated by local Hα

Abstract: Context. Use of Type Ia supernovae (SNe Ia) as distance indicators has proven to be a powerful technique for measuring the darkenergy equation of state. However, recent studies have highlighted potential biases correlated with the global properties of their host galaxies, large enough to induce systematic errors into such cosmological measurements if not properly treated. Aims. We study the host galaxy regions in close proximity to SNe Ia in order to analyze relations between the properties of SN Ia events and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
288
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(313 citation statements)
references
References 72 publications
25
288
0
Order By: Relevance
“…Hamuy et al 2000, Howell et al 2009a, Lampeitl et al 2010, Smith et al 2012, Xavier et al 2013. Rigault et al (2013) have shown this trend at the local level in SN Ia host galaxies, using local Hα surface brightness as a star-formation tracer. While all of these studies see the same general trend, the scatter in the relation is large, and the various samples give different pictures of how the trend arises.…”
Section: Spectral and Light Curve Modelingmentioning
confidence: 89%
“…Hamuy et al 2000, Howell et al 2009a, Lampeitl et al 2010, Smith et al 2012, Xavier et al 2013. Rigault et al (2013) have shown this trend at the local level in SN Ia host galaxies, using local Hα surface brightness as a star-formation tracer. While all of these studies see the same general trend, the scatter in the relation is large, and the various samples give different pictures of how the trend arises.…”
Section: Spectral and Light Curve Modelingmentioning
confidence: 89%
“…This suggests that supernova systematic uncertainties that could be expected to vary with wavelength (e.g., dust extinction or colour correction) are not likely to play a dominant role in "explaining" the tension between the local measurement of H 0 and its inference from CMB data in a standard cosmological model. Studies have sought to determine whether or not SN Ia luminosity variations relate to local environments in nearby samples (z 0.1; Rigault et al 2013Rigault et al , 2015Kelly et al 2015;Jones et al 2015;Roman et al 2017). To play a dominant role, such environmental factors must affect both the optical and J-band light curves in common.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will aim at investigating the dependence on environmental properties, such as star formation rates and metallicities, a topic of active investigation (Childress et al 2013a;Rigault et al 2013Rigault et al , 2015Jones et al 2015;Kelly et al 2015).…”
Section: Generalizing the Phillips Correctionsmentioning
confidence: 99%